Digital Accountability Management Paradox Resolving Controls with AI Blockchain Assurance for Sustainability Performance - Ahmad Rizani; Achmad Daengs GS (Journal Economic Business Innovation, 2026)
Purpose—This study analyzes how digital capabilities, governance, and accounting translate into sustainability-oriented outcomes via an integrated performance measurement system.Design/methodology/approach—This model was tested using a unique design to provide a quantitative explanation in terms of structural equation modelling (SEM) of direct effects, mediating effects, moderating effects, and resilience measures.Findings—The findings show that digital governance does not automatically result in high performance. The same is true of agile principles and controls. The same is true of modern accounting assurance. And the same is true of sustainability control systems. Instead, these outcomes are largely realized through performance measurement capabilities that resolve the paradox of balancing efficiency/accountability and sustainability agendas. This ability is believed to be crucial in turning digital resources and management into a lasting competitive edge and organizational strength. Regulatory and environmental pressures show a marginal level of influence in context, suggesting that a robust internal measurement architecture remains stable across contexts.Originality/value—This study introduces performance measurement capabilities that resolve the paradox as a unique organizational capability, expanding existing knowledge about digital transformation and sustainability accounting beyond static views of control systems. This paper expands capability-based theories of digital accountability and sustainability performance by synthesizing digital leadership, AI-blockchain assurance, agile governance, and sustainability controls within an integrated explanatory framework.Implications—Integrating digital and sustainability initiatives into learning-based performance measurement systems is strategically vital. They suggest ways in which digital accountability mechanisms can be used in institutional environments that are under pressure to transform into long-term sustainable value generators.